Painleve analysis of a class of nonlinear diffusion equations. (1996) - Chandrasekaran, P.; Ramasami, E. K.
Abstract : We study the Painleve analysis for a class of nonlinear diffusion equations. We find that in some cases it has only the conditional Painleve property and in other cases, just the Painleve property. We also obtained special solutions.